Insurance contract - Lilienthal, Gary; Ali Mohamed, Ashgar Ali; Masum, Ahmad; Ahmad, Muhamad Hassan (CLJ Malaysia Sdn Bhd, 2024)
This chapter is a brief introductory coverage of the so-called contract of insurance. In considering the meaning of the term “insurance”, it can be described as follows. One party, called the insurer, in consideration of a sum of money, called the premium, undertakes to pay to another party, called the insured, a sum of money or its equivalent on the happening of a specified event. There must be an element of uncertainty as to the “specified event”, either whether it will happen at all or when it might happen. The document issued by the insurer is evidence of the contract and is called the “policy”. The insurance policy contains the terms of the contract. In particular, it recites the risk of the insured. Generally, policies describe things the insured is required to do and will often contain exclusion clauses that exclude the liability of the insurer in certain circumstances.